Simvastatin modulates gingival cytokine and MMP production in a rat model of ligature-induced periodontitis - Mouchrek Júnior JCE; Macedo CG; Abdalla HB; Saba AK; Teixeira LN; Mouchrek AQES; Napimoga MH; Clemente-Napimoga JT; Borges AH; Tonetto MR; Pinto SCS; Bandeca MC; et al. (Dove Medical Press, 2017)
José Carlos Elias Mouchrek Júnior,1 Cristina Gomes Macedo,2 Henrique Ballassini Abdalla,2 Ana Karina Saba,1 Lucas Novaes Teixeira,1 Adriana Quinzeiro e Silva Mouchrek,3 Marcelo Henrique Napimoga,1 Juliana Trindade Clemente-Napimoga,1 Alvaro Henrique Borges,4 Mateus Rodrigues Tonetto,4 Shelon Cristina Souza Pinto,5 Matheus Coelho Bandeca,3 Elizabeth Ferreira Martinez1 1Laboratory of Cell and Molecular Biology, São Leopoldo Mandic Institute and Research Center, Campinas, 2Physiological Sciences, Piracicaba Dental School, University of Campinas, Campinas, São Paulo, 3Department of Dentistry, CEUMA University, São Luis, Maranhão, 4Department of Integrated Dental Science, University of Cuiaba, Cuiabá, Mato Grosso, 5Department of Dentistry, Ponta Grossa State University, Ponta Grossa, Paraná, Brazil Purpose: The aim of this study was to evaluate the effect of simvastatin on the synthesis of cytokines TNF-α and IL-10 and metalloproteinase (MMPs) 2 and 9 in a rat model of ligature-induced periodontitis.Materials and methods: Twenty Wistar rats were used, and a cotton ligature was place in a subgingival position encircling the entire cervix of the first molar of the left (ipsilateral) side of the mandible. The right (contralateral) side of the mandible had no ligature placed and was used as control. After the ligature placement, animals were randomly assigned to two experimental groups (n=10): 1) rats with ligature + vehicle (saline; 10 mL/kg; orally) and 2) rats with ligature + simvastatin (25 mg/kg; orally). After 14 days of treatment, the animals were euthanized by anesthetic overdose and the gingival tissue was removed and homogenized in appropriate buffer. MMP-2 and -9 release as well as the IL-10 and TNF-α levels were detected by enzyme-linked immunosorbent assay. Statistical comparison was performed by unpaired Student’s t-test, with p<0.05 representing significance.Results: No differences were observed for TNF-α production between the groups (p>0.05). However, IL-10 was upregulated in simvastatin-treated animals (1.8-fold increase) in comparison with the vehicle-treated group (p<0.05). Simvastatin reduced the gingival levels of MMP-9 (64.3%) in comparison with vehicle-treated samples (p<0.05).Conclusion: Oral treatment with simvastatin increased the release of IL-10 and reduced the MMP-9 in ligature-induced periodontitis model in rats. Keywords: cytokines, metalloproteinases, periodontal disease, simvastatin